Influence Internship Learning Effect in Business Service Sector: Using Internship Self-Efficacy as the Mediator Variable - Chun-Mei, Chou; Chien-Hua, Shen (Financial Risk and Management Reviews, 2015)
This study examines 364 tertiary students’ internship learning effect and its influencing factors to serve as a school reference for the development of internship education measures. The results show that students’ internship self-efficacy (ISE) has a significant direct effect on ‘internship learning effect (ILE)’, and ‘internship awareness (IA) ‘has a significant effect on ‘internship learning effect’ through ‘internship self-efficacy’. The influence pattern and empirical data of ‘internship awareness ‘and ‘internship self-efficacy ’ on ‘internship learning effect’ has a good fit.